PICKPOCKET DISCOURSE COMMUNITY SEEN IN OLIVER TWIST MOVIE - Swari, Utami Ratna (Fakultas Ilmu Pendidikan (FIP) Universitas Hasyim Asy'ari (Unhasy) Tebuireng Jombang, 2017)
Abstract: This study is qualitative study and focus on the sociolinguistics which studying language and society of a certain community. The emphasis of this study is discourse community. The discourse community must have all these qualities or it is not a discourse community. Swales definition sets a professional tone to the term discourse community, a central community in Oliver Twist , that is Pickpocket community. Thus, this study aiming to analyze further about the pickpocket discourse community seen in Oliver Twist movie based on the six characteristics of discourse community defined by Swales. Key words: discourse community, pickpocket, Oliver Twist